2014
DOI: 10.1891/2168-6653.28.4.225
|View full text |Cite
|
Sign up to set email alerts
|

Employer Practices for Employment of People With Disabilities: A Literature Scoping Review

Abstract: Purpose:Research on employment for people with disabilities has focused on the perspectives of people with disabilities and service providers. Empirical evidence about employer practices and their outcomes would inform the development of more targeted interventions.Method:Scoping review was conducted of literature discussing employer-focused research.Results:Research heavily concerned with employer attitudes and culture. Reports of studies of attitudes and behavior are primarily being published for an audience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Scoping reviews or scoping studies refer to a process of 'mapping' or 'scoping' the existing literature of a given research area (Arksey & O'Malley 2005). Scoping reviews are one of several methods used to review primary research (Hannes & Lockwood 2012), and have been applied widely within work and health research to identify knowledge gaps, summarize findings, and outline new types of research inquiry (Karpur 2014;McDowell & Fossey 2015;Saunders & Nedelec 2014). Scoping reviews differ from systematic reviews in that they do not involve a quality assessment of included studies or a checklist for procedures.…”
Section: Methods For Achieving Review Resultsmentioning
confidence: 99%
“…Scoping reviews or scoping studies refer to a process of 'mapping' or 'scoping' the existing literature of a given research area (Arksey & O'Malley 2005). Scoping reviews are one of several methods used to review primary research (Hannes & Lockwood 2012), and have been applied widely within work and health research to identify knowledge gaps, summarize findings, and outline new types of research inquiry (Karpur 2014;McDowell & Fossey 2015;Saunders & Nedelec 2014). Scoping reviews differ from systematic reviews in that they do not involve a quality assessment of included studies or a checklist for procedures.…”
Section: Methods For Achieving Review Resultsmentioning
confidence: 99%
“…Research in the field of disability and rehabilitation has primarily focused on individual readiness-commonly referred to as 'supply side' strategies -and overlooked the role of market factors in disability employment (Chan et al, 2010). Karpur, VanLooy, and Bruyère (2014) similarly find that disability employment researchers have primarily focused on workplace accommodation processes or general attitudes toward hiring people with disabilities. The main focus of disability and employment research is on opportunities for people with disabilities to become qualified job candidates, or to support rehabilitation professionals in helping people with disabilities obtain and maintain work placements (Chan et al, 2010).…”
Section: Advancing Disability Employmentmentioning
confidence: 99%
“…The main focus of disability and employment research is on opportunities for people with disabilities to become qualified job candidates, or to support rehabilitation professionals in helping people with disabilities obtain and maintain work placements (Chan et al, 2010). Other research has identified factors that influence employers' perceptions of hiring people with disabilities, such as attitudinal barriers and concerns about associated costs of providing accommodations (Chan et al, 2010;Karpur et al, 2014). Research on strategies to advance disability inclusion in the workforce, however, has been limited.…”
Section: Advancing Disability Employmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study examining research on employment of people with disabilities research across a 20-year period , articles about workplace accommodation, organizational culture, recruitment and hiring were published with significantly greater frequency than research on retention and advancement (Karpur, VanLooy, & Bruyère, 2014). For most employers, there remains quite a bit of work to do in improving career advancement and retention practices.…”
Section: The Importance Of Employer Practicesmentioning
confidence: 99%